Komunikasi Difabel Korban Gempa Bumi Studi Deskriptif Kualitatif Komunikasi Interpersonal VolunteerPerkumpulan SCI Spinal Cord Injury Klaten Terhadap Orang DifabelKorban Gempa Bumi 2006 Dalam Meningkatkan Motivasi Diri) - Fajarningrum, Ayu (2016)
Ayu Fajarningrum, L100110094, Difabel Communication of earthquake (Descriptive Qualitative Study Of Interpersonal Communication On Volunteer Of SCI Klaten Toward Difabel Earthquake Victims Year 2006 On Increasing Self-Motivation). Undergraduate Thesis, Communication Science Study Program, Communication and Technology Information Faculty, Muhammadiyah University Of Surakarta, 2016. Communication is important things in human being life. Here, communication become absolute thing to communicate each other's especially interpersonal communication. Actually Interpersonal communication is the important needs for keeping human being relationship. The subject of this research is volunteer and victims. While, the object of this research is volunteer group of SCI which was used interpersonal communication with difabel of SCI. The purpose of the research is to know how interpersonal communication doing by volunteer toward the difabel SCI it would build a self-confident and motivation in continuing future life. The writer adopts interpersonal communication, self and motivation. The type of this research is descriptive qualitative. On the other hand. The writer had done depth observation and interview. The result of this research show that interpersonal communication is positive. All the indicator in the theory could be show. On the first time, victims did not a self-confidence until they persuade by volunteer with family and social approach, then found other friends with the same life, confert and motive, so they can survive from life until know.